Global distribution of revenue loss from tax avoidance: Re-estimation and country results - Alex Cobham; Petr Janský (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
International corporate tax is an important source of government revenue, especially in lower-income countries. An important recent study of the scale of this problem was carried out by International Monetary Fund researchers Ernesto Crivelli, Ruud De Mooij, and Michael Keen. We first re-estimate their innovative model, and then explore the effects of introducing higher-quality revenue data from the ICTD-WIDER Government Revenue Database. Whereas Crivelli et al. report results for two country groups only, we present country-level results to make the most detailed estimates available. Our findings support a somewhat lower estimate of global revenue losses of around US500 billion annually and indicate that the greatest intensity of losses occurs in low- and lower middle-income countries, and across sub-Saharan Africa, Latin America and the Caribbean, and South Asia.
Keywords: F21; F23; H25; 330; corporate income tax; international taxation; tax avoidance; BEPS; developing countries